Supply chain management : - Shah, Janat (Pearson, 2016)
Supply Chain Management: Text and Cases presents a comprehensive, yet structured, view of logistics and supply chain management, with a focus on supply chain innovations for firms operating in competitive markets. The most significant change from the previous edition is the addition of two chapters. Chapter 11 is about supply chain contracts. Supply chain contract is emerging as a valuable instrument to coordinate various supply chains. Few popular contracts such as buyback contracts and revenue sharing contracts are discussed in depth. The other new chapter is Chapter 14. It deals with emerging field of sustainable supply chain management.